A Perspective for Developing Polymer-Based Electromagnetic Interference Shielding Composites - Zhang, Yali; Gu, Junwei (Nano-Micro Letters, 2022)
The rapid development of aerospace weapons and equipment, wireless base stations and 5G communication technologies has put forward newer and higher requirements for the comprehensive performances of polymer-based electromagnetic interference (EMI) shielding composites. However, most of currently prepared polymer-based EMI shielding composites are still difficult to combine high performance and multi-functionality. In response to this, based on the research works of relevant researchers as well as our research group, three possible directions to break through the above bottlenecks are proposed, including construction of efficient conductive networks, optimization of multi-interfaces for lightweight and multifunction compatibility design. The future development trends in three directions are prospected, and it is hoped to provide certain theoretical basis and technical guidance for the preparation, research and development of polymer-based EMI shielding composites. Highlights: 1 Bottlenecks for developing polymer based electromagnetic interference (EMI) shielding composites are proposed and inner reasons are discussed 2 Possible directions to break through bottlenecks are raised and recent advances in such directions are introduced. 3 Development trends in the future are foreseen to provide theoretical basis and technical guidance for development of polymer based EMI shielding composites.